Faktor Kesuksesan SIM-RS Berdasarkan Teori DeLone and McLean di Rumah Sakit Umum Daerah Kota Mataram - Yan Reiza Permana; Musparlin Halid; Uswatun Hasanah; Rizal Pratama Adi Putra; Ikhwan Ikhwan (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
Information systems with technology support are one of the systems that have a big role in the success of the organization. The purpose of this study is to describe the success factors of the Hospital Management Information System (SIM-RS) in the medical record installation based on the theory of DeLone and McLean which consists of six variables. namely system quality, information quality, service quality, use, user satisfaction and benefits. This research was conducted at the Mataram City Hospital (MCH) with a sample of 48 medical record officers who use a SIM-RS. The results obtained from this study according to the system quality variable that as many as 48% of medical record officers stated that the SIM-RS had quality. The information quality variable, as much as 54% of respondents stated that the SIM-RS was of high quality. Service quality variable as much as 79% of respondents said they were satisfied with the SIM-RS. The use variable as many as 43% of respondents stated that the SIM-RS was often used. The user satisfaction variable as much as 94% of respondents stated that the SIM-RS was of good quality. The benefit variable, as many as 56% of respondents stated that the SIM-RS was useful.